(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the study of the historical foundations of the origin of the epic «Manas». The author attempted to show the reflection of some traces of the relationship between the Juan and the Kyrgyz, which took place in the history of Central Asia in the late 4th and early 5th centuries AD, in the epic «Manas». Some military-political and ethnocultural aspects of the relationship between the Juan Khaganate and the Kyrgyz people in epic poetic lines according to the versions of S. Orozbakov and S. Karalaev are studied in comparison with historical sources. It is especially emphasized that Chinese historical sources allow us to reveal the historical and cultural processes hidden in certain aspects of the epic. The author suggests considering the term «zhangzhung» not only as a military and state rank, but also as a term denoting the name of the people. Thanks to the analysis of the epic lines based on the second aspect, the author managed to achieve some important historical and ethnographic results. It is concluded that the Juan-Kyrgyz ties are one of the historical foundations in the emergence of the «Manas» epic.